2014
DOI: 10.5812/asjsm.22766
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Sports Related Occurrence of Traumatic Orodental Injuries and Associated Risk Factors in High School Students in North India

Abstract: Background:Oral and dental injuries contribute to a major part of sports related injuries in children. Trauma occurring in developing years disrupts normal social functioning and brings about a major impact on quality of life due to their cumulative effect.Objectives:To assess the prevalence and causes of various sports related traumatic orodental injuries among 8 to 16 year school students along with identifying the associated risk factors in North India.Patients and Methods:A cross sectional study consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 17 publications
2
43
2
7
Order By: Relevance
“…The findings from this study support that maxillary incisors are the most frequently involved teeth in soccer‐related TDIs . In addition, the prevalence of enamel‐only and enamel/dentine fractures in this study accounted for 80% of all injured teeth.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings from this study support that maxillary incisors are the most frequently involved teeth in soccer‐related TDIs . In addition, the prevalence of enamel‐only and enamel/dentine fractures in this study accounted for 80% of all injured teeth.…”
Section: Discussionsupporting
confidence: 80%
“…Soccer‐related injuries to the head, face and neck areas represent about 3%‐10% of all soccer‐related injuries . Recent studies estimate that the frequency of soccer‐related oro‐dental injuries among amateur and professional adolescent and adult players was 0.1%‐32% . Still, prevalence studies of soccer‐related TDIs among young amateur players are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 1023 records were discarded and 81 studies were considered eligible to be fully assessed. After full‐text reading (phase‐2), 27 studies were finally included for qualitative and quantitative synthesis. Therefore, a total of 54 articles were excluded in phase‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Information regarding use of mouthguards was not available in ten of the included studies . However, it was observed that in some sports more than 80.0% of the participants wore mouthguards .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation